2021
DOI: 10.1002/ecy.3218
|View full text |Cite
|
Sign up to set email alerts
|

Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time

Abstract: Increasing effects of chronic nutrient enrichment on plant diversity loss and Increasing effects of chronic nutrient enrichment on plant diversity loss and ecosystem productivity over time ecosystem productivity over time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 66 publications
15
65
0
Order By: Relevance
“…Other studies have found that increased nutrient supply can increase soil C accumulation rates in uncultivated grassland (Crowther et al, 2019;Fornara & Tilman, 2012;Liu & Greaver, 2010;Lu et al, 2011;Seabloom et al, 2021;Yue et al, 2016), but our study builds from these globally distributed experiments and meta-analyses to demonstrate continuing, albeit slowing, long-term gains of soil C across nearly four decades. Interestingly, these results are in marked contrast to tests of nutrients and soil C storage in some annually cultivated crop fields (e.g., Khan et al, 2007), where persistent multidecadal disturbance of enriched soils has been associated with net losses of % soil C. et al, 2015).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Other studies have found that increased nutrient supply can increase soil C accumulation rates in uncultivated grassland (Crowther et al, 2019;Fornara & Tilman, 2012;Liu & Greaver, 2010;Lu et al, 2011;Seabloom et al, 2021;Yue et al, 2016), but our study builds from these globally distributed experiments and meta-analyses to demonstrate continuing, albeit slowing, long-term gains of soil C across nearly four decades. Interestingly, these results are in marked contrast to tests of nutrients and soil C storage in some annually cultivated crop fields (e.g., Khan et al, 2007), where persistent multidecadal disturbance of enriched soils has been associated with net losses of % soil C. et al, 2015).…”
Section: Discussionmentioning
confidence: 56%
“…For example, humans are increasing supplies of biologically limiting resources, such as nitrogen (N), to Earth's ecosystems (Steffen et al, 2015; Vitousek et al, 1997), resulting in significant changes in communities and ecosystems (Elser et al, 2007; Hillebrand et al, 2007; Lawes & Gilbert, 1880; Midolo et al, 2019; Simkin et al, 2016; Song et al, 2019; Vitousek et al, 1997). In grasslands, many of which are on abandoned agricultural lands, increased nutrient supplies often lead to increased productivity and soil C accumulation (Crowther et al, 2019; Fay et al, 2015; Fornara & Tilman, 2012; Seabloom et al, 2021; Ziter & MacDougall, 2013). However, increased nutrient supply rates reduce diversity in grassland ecosystems, and this diversity loss may reduce the positive effects of nutrients on productivity and soil C in the long term (Hungate et al, 2017; Isbell et al, 2013; Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we hypothesised that multiple resource additions will result in greater changes than single resource treatments. We addressed these hypotheses by leveraging data from a range of sites and assessed whether ecosystem attributes contribute to responsiveness of community change processes, because the response of a community to GCD treatments can depend on local abiotic conditions (Seabloom et al, 2021; Walker et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While the fast components of ecological acclimation, such as physiological adjustment, can be studied using experimental and observational approaches, we know much less about the rate of slow components. Experiments typically lack the spatial or temporal extent to observe species turnover or evolutionary adaptation, and may only capture transient behavior [10][11][12] . Paleoecological observations provide much of what we know about long-term ecological responses to environmental change 13 , but the data have critical gaps [15][16][17] , and current rates and magnitudes of warming exceed those observed in the past 18,19 .…”
mentioning
confidence: 99%